Special paleogeographic characteristics and changes in δ18O values in Upper Pleistocene deposits of the Moravian Plateau - Kis, Éva; Schweitzer, Ferenc; Futó, István; Vodila, Gergely; Balogh, János; Di Gléria, Mária (Hungarian Geographical Bulletin, 2011)
Our own new environment-discrimination proxies, which include beyond the traditional sedimentary parameters our newly introduced indices (fineness grade: Fg and degree of weathering: Kd), δ18O values and stratigraphic data were used in our study to compare loess-paleosol sequences with the data of mid-latitude deep-sea sediments and ice cores from Greenland. By our data from the Červený kopec section completed with other surrounding sequences, we came to the conclusion that the section consists of the last glacial (Würm) and last interglacial (Riss/Würm) deposits.The double paleosols equivalent with the MF1 soils (according to the Hungarian loess terminology) can be found together only in some places. In most of the sections only some part of the complex remained (e.g. the chernozem soil in Dolní Vĕstonice with an age of 30.9 ky BP; the forest soil in Červený kopec – Bohunice-type culture: 40.2 ky BP). The MF2 paleosol is situated in the lower part of the section and it was formed during the MIS 5 (Marine Isotope Stage).